A New Subspecies of the Genus Leistus (Coleoptera, Carabidae) from Western Caucasus - Putchkov, A.V. (Інститут зоології ім. І.І. Шмальгаузена НАН України, 2001)
Leistus (s. str.) denticollis adygeicus subsp. n. from West Caucasus (Adygeya, Caucasian
reservation, Abago pasture) is described. Its comparison analyse with nominotypical subspecies is
given. Описан Leistus (s. str.) denticollis adygeicus subsp. n. (Автономная Республика Адыгея, Кавказский государственный биосферный заповедник, пастбище Абаго). Приведен его сравнительный анализ с номинативным подвидом.